Distribution of cortical neurons projecting to the superior colliculus in macaque monkeys - Cerkevich CM (Eye and Brain, 2014)
Christina M Cerkevich,1 David C Lyon,2 Pooja Balaram,3 Jon H Kaas3 1Department of Neurobiology, University of Pittsburgh School of Medicine, Systems Neuroscience Institute, Pittsburgh, PA, USA; 2Department of Anatomy and Neurobiology, University of California, Irvine, CA, USA; 3Department of Psychology, Vanderbilt University, Nashville, TN, USA Abstract: To better reveal the pattern of corticotectal projections to the superficial layers of the superior colliculus (SC), we made a total of ten retrograde tracer injections into the SC of three macaque monkeys (Macaca mulatta). The majority of these injections were in the superficial layers of the SC, which process visual information. To isolate inputs to the purely visual layers in the superficial SC from those inputs to the motor and multisensory layers deeper in the SC, two injections were placed to include the intermediate and deep layers of the SC. In another case, an injection was placed in the medial pulvinar, a nucleus not known to be strongly connected with visual cortex, to identify possible projections from tracer spread past the lateral boundary of the SC. Four conclusions are supported by the results: 1) all early visual areas of cortex, including V1, V2, V3, and the middle temporal area, project to the superficial layers of the SC; 2) with the possible exception of the frontal eye field, few areas of cortex outside of the early visual areas project to the superficial SC, although many do, however, project to the intermediate and deep layers of the SC; 3) roughly matching retinotopy is conserved in the projections of visual areas to the SC; and 4) the projections from different visual areas are similarly dense, although projections from early visual areas appear somewhat denser than those of higher order visual areas in macaque cortex. Keywords: visual cortex, superior colliculus, frontal eye field, posterior parietal cortex, visual system